Evaluating Corn Yield Response to Nitrogen According to Soil Parameters in Midwest American Farmland - Joaquin Enrria; Carlos Hernández; Francisco Palmero; Ana Julia Paula Carcedo; Ignacio Antonio Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2024)
Nitrogen (N) availability is one of the most common factors limiting corn yields. Corn N requirements are determined mainly by seasonal conditions and soil characteristics. An inaccurate N fertilization program could compromise the economic and environmental sustainability of the activity. The aim of this study was to determine the influence of soil characteristics (clay, sand, water content, pH water, and organic matter) on corn’s yield response to N fertilization in the midwestern USA. A published data set was analyzed, containing 49 experiments (year-site combinations) related to corn N fertilization and soil characteristics in eight midwestern American states. The soil variables were analyzed to classify the experiments into two clusters. An econometric spatial model was fitted to explore the corn yield response to nitrogen in each cluster. Grain yield response to N total amount differed between clusters. Moreover, yield estimated values presented were significant for yield potential to 0 N lb/a, Cluster 1= 149 bu/a and Cluster 2= 165 bu/a, and maximum yield, 289 bu/a and 275 bu/a for Cluster 1 and Cluster 2, respectively. The overall response in yield to a unit of N (lb/a) was 1 bu/a to Cluster 1 and 0.85 bu/a to Cluster 2. These findings could lead to further analysis to be carried out considering larger soil parameters in wider environmental conditions.
Keywords: corn; nitrogen response; clusters; soil characteristics; spatial data